FAIRsharing – a globally inclusive curated resource on data and metadata standards - Lister, Allyson (My University, 2023)
FAIRsharing is a curated resource on data and metadata standards, interrelated to databases and data policies, across all disciplines. We will find out what documentation FAIRsharing holds for African research standards, databases, and more.
Allyson Lister ORCID: 0000-0002-7702-4495; LinkedIn: /in/allysonlister  Allyson Lister is the FAIRsharing Content & Community Lead at the University of Oxford. With a background in data standardisation, ontologies, semantic data and integration, she is responsible for FAIRsharing content, as well as for the collaborations with users and outreach across all research domains. Allyson is also an EOSC Future / RDA Domain Ambassador (for standards, databases and policies), and is a co-chair of two RDA working groups. About this webinar This webinar session is part of a series co-organized by UbuntuNet Alliance and Access 2 Perspectives as part of the ORCID Global Participation Program. About ORCID ORCID is the persistent identifier for researchers to share their accomplishments (research articles, data, etc with funding agencies, publishers, data repositories, and other research workflows. About AfricArXiv AfricArXiv is a community-led digital archive for African research communication. By enhancing the visibility of African research, we enable discoverability and collaboration opportunities for African scientists on the continent as well as globally.